2020
DOI: 10.1123/japa.2019-0221
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Function of Forearm Muscle in Postmenopausal Women With Type 2 Diabetes

Abstract: Changes in the hemodynamic function of muscle are speculated as a causal mechanism for reduced motor capabilities with aging in Type 2 diabetes mellitus (DM). The focus of this study was to evaluate changes in muscle oxygenation during sustained force production in postmenopausal women with DM compared with controls. Near-infrared spectroscopy was used to monitor deoxyhemoglobin and oxyhemoglobin in the flexor digitorum superficialis. Sensorimotor function and health state covariates were also assessed. Increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Tactile sensitivity loss due to peripheral neuropathy (PN) has been implicated as the primary cause of both sensory and motor deficits in the hands and feet of PwDM [7][8][9][10]; however, our recent work has demonstrated that motor changes in PwDM occur independent of such tactile impairment, and appear to be unrelated to disease duration and severity [2][3][4][5]11]. Our data indicate other physiological factors such as vascular dysfunction and functional cortical changes as the underlying mechanism for sensorimotor changes in PwDM [2][3][4][5][11][12][13][14]. Due to the confluence of multiple systemic changes in the bodies of PwDM, the contribution of multiple systems−including sex hormone changes and impaired global hemodynamic function−to sensorimotor dysfunction prior to PN diagnosis in PwDM is fully plausible.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Tactile sensitivity loss due to peripheral neuropathy (PN) has been implicated as the primary cause of both sensory and motor deficits in the hands and feet of PwDM [7][8][9][10]; however, our recent work has demonstrated that motor changes in PwDM occur independent of such tactile impairment, and appear to be unrelated to disease duration and severity [2][3][4][5]11]. Our data indicate other physiological factors such as vascular dysfunction and functional cortical changes as the underlying mechanism for sensorimotor changes in PwDM [2][3][4][5][11][12][13][14]. Due to the confluence of multiple systemic changes in the bodies of PwDM, the contribution of multiple systems−including sex hormone changes and impaired global hemodynamic function−to sensorimotor dysfunction prior to PN diagnosis in PwDM is fully plausible.…”
Section: Introductionmentioning
confidence: 65%
“…Recently, our group found no differences in tactile function of postmenopausal female PwDM as compared to age-and sex-matched controls during the assessment of upper extremity muscle hemodynamics [13]. This finding was intriguing as abnormal hemodynamic function of upper extremity muscle was found in PwDM and supports vascular dysfunction as a potential source of global sensorimotor changes in PwDM [10,15], particularly in females as females have a higher overall risk of cardiovascular complications with age; however, the lack of between group tactile function differences challenged this point of view.…”
Section: Introductionmentioning
confidence: 73%
“…40 However, DM is also associated with impaired hyperemic responses, endothelial dysfunction, and microvascular dysfunction. 13,16,41,42 DM has also recently been linked to pathological neurovascular decoupling in PwDM (as reviewed in Ref. 43) and conflicting reports of reduced cerebral blood flow.…”
Section: Functional Cortical Activity and Tissue Oxygenationmentioning
confidence: 99%
“…12 Our data point toward other factors, such as alterations in motor unit structure-function and reduced hemodynamic function of muscle and the cortex as underlying mechanisms for these sensorimotor changes. 13 Due to the confluence of multiple systemic changes in the body in PwDM, the contribution of impaired or altered cortical function to sensorimotor dysfunction prior to PN diagnosis in PwDM is fully plausible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation